PENERAPAN MODEL PEMBELAJARAN PROBING PROMPTING PADA PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS V SD INPRES LABAT - Tefa, Ester Aprianti; Manafe, Yetursance; Normin, Treesly Y. (SINERGI : Jurnal Riset Ilmiah, 2024)
This research is based on the existence of problems in classroom learning that cause low student learning activity, especially in the subject of Pancasila Education material Gotong Royong in the Environment Chapter 4 I and My Environment Learning 2. This research aims to increase the learning activity of students in Pancasila Education class V through the application of the Probing Prompting learning model. The research method used is Classroom Action Research (PTK) which is carried out in 2 cycles. Each cycle has four stages, namely: planning, implementation, observation and reflection. This research was conducted at SD Inpres Labat, Kupang City. The subject of the study was class V students of SD Inpres Labat which consisted of 25 students. Data collection techniques are in the form of observations and tests. The results of the study show that learning using the Probing Prompting model can increase the learning activity of students in grade V of SD Inpres Labat. In the first cycle, the students' learning activity got good criteria with a percentage of 65%, while in the second cycle they got very good criteria with a percentage of 88.75%. So, the Probing prompting learning model can increase students' learning activity.